2019
DOI: 10.3847/1538-3881/ab4136
|View full text |Cite
|
Sign up to set email alerts
|

KELT-24b: A 5MJ Planet on a 5.6 day Well-aligned Orbit around the Young V = 8.3 F-star HD 93148

Abstract: We present the discovery of KELT-24 b, a massive hot Jupiter orbiting a bright (V=8.3 mag, K=7.2 mag) young F-star with a period of 5.6 days. The host star, KELT-24 (HD 93148), has a T eff = -+ 6509 49 50 K, a mass of M * =

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Less challenging follow-up would be spin-orbit alignment through Rossiter-Mclaughlin, where the signal is expected to be >200 m s −1 and the transit timescale ( 5 h) is much shorter than the rotational jitter (1.65 days). Recent measurements of stellar obliquity in young planetary systems have found that they are generally aligned with their host stars (e.g., Rodriguez et al 2019;Zhou et al 2020;Wirth et al 2021), suggesting that these planets formed in situ or migrated through their protoplanetary disk. However, the number of misaligned systems even around older stars is 10% (varying with spectral type and planet mass; Fabrycky & Winn 2009; Morton & Winn 2014;Campante et al 2016).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Less challenging follow-up would be spin-orbit alignment through Rossiter-Mclaughlin, where the signal is expected to be >200 m s −1 and the transit timescale ( 5 h) is much shorter than the rotational jitter (1.65 days). Recent measurements of stellar obliquity in young planetary systems have found that they are generally aligned with their host stars (e.g., Rodriguez et al 2019;Zhou et al 2020;Wirth et al 2021), suggesting that these planets formed in situ or migrated through their protoplanetary disk. However, the number of misaligned systems even around older stars is 10% (varying with spectral type and planet mass; Fabrycky & Winn 2009; Morton & Winn 2014;Campante et al 2016).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…5: This companion was detected with AO imaging by Rodriguez et al (2019) using Keck/NIRC 2, but is also listed in the Gaia DR2, whose astrometry was used by this team to verify the equidistance and common proper motion of this companion with the exoplanet host star MASCARA-3 A, as done in this study. 6: This companion was already reported by Nielsen et al (2019), who proved its companionship with the exoplanet host star WASP-175 A with Gaia DR2 astrometry, consistent with the results derived here.…”
Section: Comments On Individual Objectsmentioning
confidence: 93%
“…d This companion of the exoplanet host star HD 85628 A was discovered by Dorval et al (2020) in the Gaia DR2, who found its parallax and proper motion consistent with that of the exoplanet host star, confirmed by the astrometric analysis, presented here. e This companion was detected with AO imaging by Rodriguez et al (2019) using Keck/NIRC 2, but is also listed in the Gaia DR2, whose astrometry was used by this team to verify the equidistance and common proper motion of this companion with the exoplanet host star MASCARA-3 A, as done in this study. f This companion was already reported by Nielsen et al (2019), who proved its companionship with the exoplanet host star WASP-175 A with Gaia DR2 astrometry, consistent with the results derived here.…”
Section: Detected Companions Of Exoplanet Hostsmentioning
confidence: 98%